Nominal scale as alternative service quality evaluation : study case of hacienda bugambilias hotel, Mexico - Urcádiz Cázares, Francisco Javier (2021)
Fil: Urcádiz Cázares, Francisco Javier. Instituto Tecnológico Nacional de México; México.